Electricity Theft in Kampala and Potential ICT Solutions - Mbabazi Mutebi, Ruth; Sansa Otim, Julianne; Okou, Richard; Sebitosi, Ben (Springer, Cham, 2014)
Electricity theft is the main source of non-technical losses in electricity distribution utilities. This paper presents data from an ongoing research to study the causes of electricity theft in Kampala, Uganda and people’s response to the efforts being made to reduce it. Our study reveals that electricity theft in Kampala is largely due to economic reasons and corruption within the utility company. It confirms that people perceive electricity theft as the utility’s problem and are not willing to report electric theft suspects. We propose ICT technologies to encourage consumer participation in reducing electricity theft.
Keywords: Energy; Electricity distribution; Electricity theft; Non-technical losses; ICT; Mobile applications; Consumer participation